A novel approach to ammonia synthesis from hydrogen sulfide. (19th January 2021) - Ghavam, Seyedehhoma; Garcia-Garcia, Guillermo; Styring, Peter
Abstract: There are a number of shortcomings for currently-available technologies for ammonia production, such as carbon dioxide emissions and water consumption. We simulate a novel model for ammonia production from hydrogen sulfide through membrane technologies. The proposed production process decreases the need for external water and reduces the physical footprint of the plant. The required hydrogen comes from the separation of hydrogen sulfide by electrochemical membrane separation, while the required nitrogen is obtained from separating oxygen from air through an ion transport membrane. 10% of the hydrogen from the electrochemical membrane separation along with the separated oxygen from the ion transport membrane is sent to the solid oxide fuel cell for heat and power generation. This production process operates with a minimal number of processing units and in physical, kinetic, and thermal conditions in which a separation factor of ~99.99% can be attained. Graphical abstract: We propose a new synthesis route for ammonia production using hydrogen sulfide which is based on separation techniques using different types of membranes (EMS and ITM). Image 1 Highlights: Ammonia can be produced from hydrogen sulfide via membrane technology. The proposed process consumes less water compared to a water electrolyzer. Small physical footprint with fewer process steps compared to other processes. This process does not produce pollutants. The process is energy intensive compared to other ammonia production technologies.